Running form how to run faster and prevent injury - Anderson, Owen 1947- (Human Kinetics, 2019)
For many runners, running technique is an afterthought--one they don't think about until an injury or plateau keeps them from achieving their goals. Running Form underscores the importance of proper form and shows you how to elevate your performance to the greatest possible extent with the smallest risk of injury